2016
DOI: 10.1016/j.jmapro.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Surface finish control by electrochemical polishing in stainless steel 316 pipes

Abstract: Electrochemical machining (ECM) is a non-conventional machining process which is based on the localised anodic dissolution of any conductive material. One of the main applications of ECM is the polishing of materials with enhanced characteristics, such as high strength, heat-resistance or corrosion-resistance, i.e. electrochemical polishing. The present work presents an evaluation of the parameters involved in the ECM of Stainless Steel 316 (SS316) with the objective of predicting the resulting surface finish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…As the pulse‐pause ratio was constant for the whole sample, only a change in the electrolyte composition along the electrolyte flow is assumed to change the electrochemical conditions and result in different surface qualities. A high current density is supposed to result in a reflective surface, whereas a low current density result in a rough surface as the passive film is not or only inhomogeneously removed [1]. Nevertheless, the reported results were not unambiguously.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As the pulse‐pause ratio was constant for the whole sample, only a change in the electrolyte composition along the electrolyte flow is assumed to change the electrochemical conditions and result in different surface qualities. A high current density is supposed to result in a reflective surface, whereas a low current density result in a rough surface as the passive film is not or only inhomogeneously removed [1]. Nevertheless, the reported results were not unambiguously.…”
Section: Discussionmentioning
confidence: 86%
“…Electrochemical machining is not only used for generating profiles that cannot be gained with any other process, but also for achieving high quality polished surfaces without undesirable tensile residual stresses. Investigations on ferrite‐pearlite 42CrMo4 showed that optically different surface areas are formed by electrochemical machining, varying between a shiny (reflective) and a dark (rough) surface appearance already after one machining step [1]. A reflective surface can be generated by micro‐smoothing which results from suppression of the influence of surface defects and crystal orientation and depends on the passivation behavior and on the chemical and microstructural composition of the material [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…The work described in this paper is part of a project where a multiphysics ECM simulation model was constructed by the authors, originally in a 2D environment, further developed into a 3D computational simulation, and subsequently linked with a real-world application example [23].…”
Section: Methodsmentioning
confidence: 99%
“…Like overpotential, current density must be sufficiently high to maintain the proper dissolution of metal, but it must not be too high. The interplay between current density and overpotential plays a deciding factor in the type of surface finish produced by electrochemical polishing, as seen by (Gomez-Gallegos, Mill, & Mount, 2016), who performed electrochemical polishing of 316 stainless steel pipes.…”
Section: Electropolishingmentioning
confidence: 99%
“…Different surface finishes of 316 SS as a function of current density and overpotential(Gomez-Gallegos et al, 2016).The rhomboids inFigure 15represent areas where a non-uniform surface finish was achieved. These regions are also referred to as being below the oxygen evolution potential, and at it.…”
mentioning
confidence: 99%